Pengukuran kerja dengan metode work sampling di Kasir Minimarket Kenjeran UD. XYX - Deviyanti , I Gusti Ayu Sri; Widari, Nyoman Sri; Fais, Moh Ainul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The operational efficiency of minimarkets is highly dependent on the performance of cashiers, who often face the challenges of idle time and workload fluctuations. This study aims to analyze the work efficiency of the cashiers of Kenjeran Minimarket UD. XYX using the work sampling method. Observations were conducted for 10 days with a confidence level of 95% and a level of accuracy of 5%. The results show an average active working time of 90%, with idle time of around 10%. Certain days reach a maximum efficiency of 96.7%, while other days record the lowest efficiency of 80%. These fluctuations remain within the limits of statistical control, indicating the consistency of the cashier's work. To improve efficiency, optimization of work schedules, additional training, and the use of automated technology are recommended. This study shows that work sampling is effective in identifying idle time and designing performance improvement strategies